Epidemiology of typhoid fever in the Philippines during the last six decades from 1960-2019: a profile and its trend - G. Sambawa, Nihaya; D. Mangotara, Rosnia; Balt, Arafat M.; J. Demayo, Chin-Chin; G. Demayo, Cesar (Intelektual Pustaka Media Utama, 2024)
Regardless of the numerous reviews and publications on typhoid fever in the Philippines, it continues to be an issue regarding public health. Using data obtained from the Philippine Health Statistics (PHS), this study examined trends in typhoid fever mortality across an interval of six decades in the Philippines. The mortality and morbidity rates of typhoid fever were analyzed to discover trends of change for each year, age group, sex, and area. The Microsoft Excel software tool became used for all data analysis. The results show a decrease in typhoid fever fatality rates in the Philippines over the previous year. In terms of sex-specific deaths, males outnumbered females. The individuals aged 70 and older have the highest death rates when it comes to age-specific mortality rates. In the Philippines, Region I also has the highest mortality rate from typhoid fever. For instance, the Autonomous Region of Muslim Mindanao (ARMM) has the lowest mortality rate from typhoid fever. The highest average morbidity rate is in the Cordillera administrative region (CAR), while the lowest is in Region IVB. To eliminate typhoid fever in the next few years and to completely combat typhoid fever throughout the years, educational campaign awareness or intimate knowledge must be conducted locally and globally.